Prevalence and relation to underground exposure of radiological irregular opacities in South Wales coal workers with pneumoconiosis. - Cockcroft, A (1983)
A total of 124 coal workers and ex-coal workers receiving disability benefit for coal worker's pneumoconiosis and routinely reattending the Cardiff Pneumoconiosis Medical Panel during a 10-week period were studied. Those with complicated pneumoconiosis were excluded. Their current chest radiographs and their chest radiographs at the time of certification were read in random order by three readers using the 1980 ILO Classification of Radiographs. An irregularity score was derived from the readings. The x-ray findings were examined for changes since certification and for relationships with age, smoking, and underground coal work exposure. One-fifth of the current radiographs showed mainly irregular opacities, whereas nearly all of those from the time of certification showed mainly irregular opacities, whereas nearly all of those from the time of certification showed mainly rounded opacities. Irregular opacities were related to age, smoking, and underground exposure. The exposure effect remained after excluding the older men. The findings suggest that radiological irregular opacities, and their associated pathology and lung function changes, commonly develop in coal workers with pneumoconiosis and should be considered part of the condition.